Effects of Handling on Hatchability of Eggs of the Leatherback Turtle, Dermochelys coriacea (L.) - Chan, Eng Heng; Salleh , H. U.; Liew, Hock Chark (1985)
The infertility rate among clutches of leatherback sea turtle (Dermochelys coriacea) eggs incubated in the hatchery at Rantau A bang, Malaysia is estimated at 22%. Variance in hatchability among fertile clutches ranges from 35.7- 96. 7% (x = 78%) for eggs handled with maximum care. For such eggs hatchability did not show a correlation with the time between oviposition and reburial. Leatherback eggs can tolerate rough handling only up to 5 hours after oviposition. Beyond this threshold, careful handling to prevent rolling, bumping, rotation and disorientation of the vertical axis will enhance hatch rates.